2001
DOI: 10.2466/pr0.2001.88.1.123
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Achievement Motives, Goal Orientations, Intrinsic Interest, and Academic Achievement

Abstract: This study investigated the effects of approach and avoidance achievement motives (the motive to achieve success and the motive to avoid failure) on three goal orientations (mastery, performance-approach, performance-avoidance goals) and the effects of goal orientations on intrinsic interest in learning and academic achievement for 157 tenth and 135 eleventh grade students of a Japanese girls' high school. Structural equation modeling indicated that mastery goals arose mainly from the motive to achieve success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 26 publications
(21 reference statements)
2
31
1
Order By: Relevance
“…Nevertheless, it should be noted that our findings are not too dissimilar from those of Tanaka and Yamauchi (2001), who applied the hierarchical model of motivation to a sample of Japanese high school girls.…”
Section: Discussioncontrasting
confidence: 57%
“…Nevertheless, it should be noted that our findings are not too dissimilar from those of Tanaka and Yamauchi (2001), who applied the hierarchical model of motivation to a sample of Japanese high school girls.…”
Section: Discussioncontrasting
confidence: 57%
“…Existing studies have shown that both mastery and performance-approach goals influence academic performance directly (Church, Elliot, & Gable, 2001;Durik, Lovejoy, & Johnson, 2009;Senko & Miles, 2008;Tanaka & Yamauchi, 2001;Vansteenkiste, Simons, Lens, Soenens, & Matos, 2004;Wolters, 2004) and indirectly via other motivational constructs such as effort (Dupeyrat & MarinĆ©, 2005;Fenollar et al, 2007), excitement and persistence (Simons, Dewitte, & Lens, 2004), interestbased studying (Senko & Miles, 2008), task disengagement (Kaplan & Maehr, 2002;Liem, Lau, & Nie, 2008) and peer relationship (Levy, Kaplan, & Patrick, 2004;Liem et al, 2008). This evidence suggests the need for educators to cultivate a classroom environment that emphasises the saliency of mastery and performance-approach goals as these goals are effective in promoting learning.…”
Section: Achievement Goals and Academic Performancementioning
confidence: 90%
“…Correlational analyses within the framework of structural equation modeling (SEM) have yielded findings showing the positive effect of mastery goals on academic performance (Tanaka & Yamauchi, 2001;Vansteenkiste, Simons, Lens, Soenens, & Matos, 2004). Similarly, academic performance is associated positively with students' orientation of performance-approach goals (Church et al, 2001;Durik, Lovejoy, & Johnson, 2009;Senko & Miles, 2008;Wolters, 2004), and negatively with performance-avoidance goals (Durik et al, 2009;Elliot et al, 1999).…”
Section: Introductionmentioning
confidence: 99%